Le décor architectural Artuqide en pierre de Mardin placé dan son contexte régional : contribution à l'histoire du décor géométrique et végétal du Proche-Orient des XIIe-XVe siècles - Beyazit, Deniz, (Archaeopress archaeology., 2015)
This volume studies the architecture of the city of Mardin in South-east Anatolia produced under the patronage of the Artuqids, whose influence held sway from c. 1101-1409.